DEVELOPMENT OF PHYSICS BASED ON PHYPOX APPLICATION WITH SMARTPHONE ACOUSTIC SENSOR ON FREE-FALL MOTION MATERIALS - Rio Sebastian; Handoyo Saputro; Eko Budiyono; Hidayati Hidayati; Puji Hariati Winingsih (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
This study aimed to produce and determine the feasibility and response of Physics Props Based on the Phypox Application with a Free Fall Motion Material Smartphone Acoustic Sensor. This type of research is research and development according to Sugiyono, (2017) which is simplified into eight stages which include potential and problems, information collection, product design, product validation, product revision, product trials, product revision, and the final product. The subjects of this study consisted of 3 validators and 15 learners. Data analysis was carried out by descriptive analysis according to Setyo Budiwanto, (2017: 18) which used a Likert scale to determine the response criteria. The results of this study were obtained including: (1) Phypox Application-Based Physics Props with Smartphone Acoustic Sensors on Free Fall motion materials therewith the manual book; (2) The feasibility test of props with a media expert assessment of 25% is very good, 67% is good, and 8% is bad, the material expert assessment is 33% very good and 67% good, and the teacher's assessment is 57% very good, 33% good, and 10% bad (3) The readability test of the learners' response to the props obtained 21% strongly agree, 72% agree, 7% disagree, and 1% strongly disagree. Based on the results of the study, it can be concluded that the props developed are suitable for learning physics.